Pengaruh Current Ratio (CR), Debt To Equity Ratio (DER) dan Net Profit Margin (NPM) terhadap Return On Asset (ROA) pada PT Arwana Citra Mulia Tbk - Happy Angeliani Purba; Rahmadi Rahmadi; Tora Fahrudin (Program Pascasarjana STIE Amkop Makassar, 2025)
The focus of this research is publicly listed ceramic companies, one of the sectors experiencing rapid growth due to increasing market demand. This development can be analyzed through profitability ratios. This study aims to evaluate and analyze the profitability of the selected sample using the current ratio (CR), debt to equity ratio (DER), and net profit margin (NPM) as independent variables, which are related to the return on assets (ROA) ratio as the dependent variable. It was found that among the three publicly listed ceramic manufacturing companies, PT Arwana Citra Mulia (ARNA) is the only company in the building products and equipment industry with the most promising profitability, with a net profit difference of up to IDR 500 Billion compared to the other two similar companies in the 2022 and 2023 periods. As a result, ARNA was selected as the sole sample in this study. The research findings indicate that all independent variables have a significant influence of 81.6% on the dependent variable based on the coefficient of determination analysis. Additionally, separately, CR and DER each show a positive influence on ROA, while the NPM ratio shows a negative influence on ROA.